# Simplify and solve the linear equation: 15(y - 4) - 2(y - 9) + 5(y + 6) = 0

**Solution:**

We will be applying distributive property and then transpose variables to one side and constants to another side to form a linear equation.

15(y - 4) - 2(y - 9) + 5(y + 6) = 0

⇒ 15y - 60 - 2y + 18 + 5y + 30 = 0 [Using distributive property]

⇒ 18y - 12 = 0

⇒ 18y = 12

Hence,

y = 12/18

y = 2/3

**Video Solution:**

## Simplify and solve the linear equation: 15(y - 4) - 2(y - 9) + 5(y + 6) = 0

### NCERT Solutions Class 8 Maths - Chapter 2 Exercise 2.5 Question 8

**Summary:**

The solution to the given equation 15(y - 4) - 2(y - 9) + 5(y + 6) = 0 after simplifying is y = 2/3